PENGARUH CELEBRITY ENDORSER DAN WOM TERHADAP KEPUTUSAN PEMBELIAN MOTOR YAMAHA: THE EFFECT OF CELEBRITY ENDORSER AND WOM ON PURCHASE DECISION OF YAMAHA MOTOR - Bobbi Shandy (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This research aim is to examine the effect of selected purchase decision variables, i.e., celebrity endorser and WoM (Word of Mouth) on purchasing decision in Jambi city. Data analyzes used multiple linier regression, where independent variables are celebrity endorser and WoM,and dependent variable is purchase decision. Primary data is gathering by questionaries delivery. The result showed that both celebrity endorser and WoM has significant influencing on purchasing decision. Hence Yamaha Corportaion should enlarge celebirity eondorsed and WoM as marketing tool to overcome competition. Keywords: Celebrity Endorser, WoM, and Purchase Decision